Works of Oleg Pavlov in Context of Literary Reflection: A Review of Research - N. A. Valyanov (Научный диалог, 2025)
This article addresses the issue of literary reflection on the artistic legacy of contemporary Russian writer Oleg Pavlov. The study is based on critical and journalistic articles, literary analyses of the author’s works, and selected literary pieces. It presents an attempt at a systematic description, generalization, and analysis of Oleg Pavlov’s poetics. For the first time, the article proposes a periodization of the writer’s oeuvre. The author identifies and interprets the classical stages of Pavlov’s creative biography — early (“biographical”), mature (“critical-journalistic”), and late (“reflective”). It is established that literary criticism has offered a mixed assessment of the writer’s artistic mastery, presenting contradictory judgments ranging from condescending and tolerant to sharp and accusatory. On one hand, his prose is associated with the classical literary tradition; on the other hand, a cliché of the “gloomy” writer has emerged. The article highlights a sustained interest in Oleg Pavlov’s works within academic literary studies, identifying mythopoetic, philosophical, historical-cultural, and linguistic research directions. The author concludes that current philological reflection opens up research perspectives in the study of Pavlov’s poetics as a representative of “new realism” in contemporary Russian literature.